A Method for Solving Fredholm Integral Equations of the First Kind Based on Chebyshev Wavelets (Analysis in Theory and Applications, 2013)
In this paper, we suggest a method for solving Fredholm integral equation of the first kind based on wavelet basis. The continuous Legendre and Chebyshev wavelets of the first, second, third and fourth kind on $[0,1]$ are used and are utilized as a basis in Galerkin method to approximate the solution of integral equations. Then, in some examples the mentioned wavelets are compared with each other.
Keywords: First kind Fredholm integral equation; Galerkin and Modified Galerkin method; Legendre wavelets; Chebyshev wavelets.